What contributes to spelling in Arabic? A cross-sectional study from first to sixth grade. Issue 1 (2nd January 2017) - Asadi, Ibrahim A.; Ibrahim, Raphiq; Khateb, Asaid
ABSTRACT: This study aimed at examining the contribution of various cognitive and linguistic variables to spelling processes among native Arabic-speaking children from first to sixth grade. For this purpose, measures of phoneme awareness (PA), orthographic, morphological, lexical and syntactic knowledge were collected, together with working memory and speed of processing indexes. The analysis was conducted on a large and representative sample using path models. The results revealed that, together with the consistent contribution of PA and orthography, morphology played an important role in predicting spelling. Furthermore, our findings suggested that Arabic orthography, even the vowelised version which is considered as transparent (since it provides the reader with the full phonological information), behaved as other deep orthographies in spelling. These findings are discussed in the context of the unique characteristics of the Arabic language and its orthographic system.